Modeling and Forecasting the Implied Volatility of the WIG20 Index - Buszkowska-Khemissi, Eliza; Płuciennik, Piotr (Uniwersytet Łódzki, 2007)
The implied volatility is one of the most important notions in the financial market. It informs about the volatility forecasted by the participans of the market. In this paper we calculate the daily implied volatility from options on the WIG20 index. First we test the long memory property of the time series obtained in such a way, and then we model and forcast it as ARFIMA process
Keywords: implied volatility; GARCH; ARFIMA; forecasting